Perancangan Aplikasi Manajemen Kepegawaian Berbasis Web Menggunakan Framework Laravel di PT. Asian Isuzu Casting - Ririn Rinasty Br. Sinulingga; Andrew Fernando Pakpahan (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
The Employee Management System is an employee data management container that can be managed with accurate information systems. Employee data management at PT. Asian Isuzu Casing Center still uses Microsoft Excel. The expected usefulness of this study is 3, namely 1) Improving employee performance in carrying out tasks. 2) Saving time in searching for stored data. 3) making it more easly for employees to manage data anywhere and anytime 4) Reducing unexpected losses due to irregular data. The methodology used in this study is the SDLC (System Development Life Cycle) method which consists of five stages, among others, (1) Needs Analysis, (2) System Design, (3) Coding, (4) Testing and (5) Implementation. The research objectives are expected to produce an Employee Management System information system at PT. Asian Isuz Casting Center. From the research that has been done, the authors, the authors conclude that, ((1) Information systems are made and components are running well. (2) This system can help facilitate the creation of employee data reports at PT. AICC. (3) This information system can create data reports and data permissions. (4) This information system can display employee statistics